Cheonggyecheon Medley: A Dream of Iron - Kyung Kun Park, Kelvin (South Korea : Kyungmi, Kim ; Hwayoung, Lee, 2010)
In the Cheonggyecheon district of Seoul, merchants started casting scrap metal salvaged from military hardware after the Japanese occupation. Generations later, iron workers continue their labor by hand in a gentrifying city and in an era where technology has far surpassed their industrial skills. Filmmaker Kelvin Kyung Kun Park locates his fevered experimental dream in this waning world, addressing his deceased grandfather who once ran his own scrap metal business. Drawing clues from fragments of dreams and myths related to metal, the film reveals the secret alchemy of third world modernity in Cheonggyecheon, where this obsolete form of manual labor still survives. The film's stream-of-consciousness narration, haunting archival footage, and palpable aural and visual textures question whether society has progressed or regressed under the specter of technology.
Verzio Film Festival Submission
Duration: 01:19:00
Verzio Film Festival Submission
Keywords: Documentary films